2017
DOI: 10.1080/13548506.2016.1271953
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns and predictors of bullying roles among adolescents in Vietnam: a school-based cohort study

Abstract: Although many cross-sectional studies have examined bullying experiences and correlated factors among adolescents in schools, relatively little is known about the extent to which bullying roles are stable or fluid over time. This short-term quantitative longitudinal study in Vietnam examined temporal patterns and predictors of bullying roles over an academic year. A total of 1424 middle and high school students aged 12-17 years completed two anonymous, self-administered questionnaires six months apart in 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 57 publications
0
22
3
10
Order By: Relevance
“…Finally, Shams et al (2017) discovered that children who had witnessed violence between their parents were more likely to show bullying behaviors (cyber and traditional perpetration and victimization was included). However, Le et al (2017) found that witnessing violence between their parents was a significant predictor of cyberbullying perpetration, but not in case of victimization.…”
Section: Contextual Family Variablesmentioning
confidence: 82%
See 3 more Smart Citations
“…Finally, Shams et al (2017) discovered that children who had witnessed violence between their parents were more likely to show bullying behaviors (cyber and traditional perpetration and victimization was included). However, Le et al (2017) found that witnessing violence between their parents was a significant predictor of cyberbullying perpetration, but not in case of victimization.…”
Section: Contextual Family Variablesmentioning
confidence: 82%
“…There were 6 (18%) studies which focused only on contextual family variables (Abdulsalam et al 2017;Çakır et al 2016;Chen et al 2018;Garmy et al 2018;Marret and Choo 2017;Shaheen et al 2018). However, there were 9 more studies (26%) which took into account such variables (Bevilacqua et al 2017;Beyazit et al 2017;Buelga et al 2017;Doty et al 2017;Garaigordobil and Machimbarrena 2017;Gómez et al 2017;Le et al 2017;Shams et al 2017;Uludasdemir and Kucuk 2018). The following variables were included: Family composition, family conflict, family's socioeconomic status, parents' education level, parental employment situation, family's home degree of rurality, parents' age, technological competence, stress, and parents' city of residence.…”
Section: Contextual Family Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lessons from anti bullying programmes are reviewed by Menesini and Salmivalli (2017). Le et al (2017) draw attention to the need to link anti-bullying programmes to mental health promotion, and to focus on peer social relationships more broadly, including with the engagement of family members, as relevant. Sherr et al (2017) show that effective changes in institutions can alleviate violence either by structural and code of conduct interventions or policy changes that avert such placements or expedite onward movement to family type environments.…”
Section: Reform Within Schoolsmentioning
confidence: 99%